STUDY ON SMA MIXTURE BY ORTHOGONAL EXPERIMENTAL DESIGN METHOD - Van Thanh, Dang; Van Tinh, Pham (Journal of Forestry Science and Technology, 2017)
Stone Matrix Asphalt (SMA) is a new type of asphalt concrete which has been applying in many countries over the world for highway building. This is a kind of hot asphalt created by mixture of plastic mastic that fills pores of interrupted gradation macadam formed according to the Macadam principle. By orthogonal experimental design method and asphalt concrete experiments in laboratory such as Marshall stability test, Residual stability test and Rutting test, this study evaluates the impact of several factors of material composition including asphalt content factors, fiber content and mineral filler content to the basic features of SMA mixture used in pavement construction presented in this paper. Research results indicate that the influence of these factors on the basic features of SMA mixture is clearly noticeable. The study also recommends the optimal values of asphalt content, fiber content and mineral filler content used for SMA-16 mixture, in turn of 6.2%; 0.30% and 10.5%, respectively.